2023
DOI: 10.4194/aquast993
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Major Constraints in Scylla Mud Crabs Grow-out Culture and Its Mitigation Methods

Abstract: Scylla mud crabs are economically important portunid species for aquaculture in many countries. However, mass production of mud crabs as a supply of seafood is still difficult up-to-date. This review aimed to provide an overview of the major constraints faced in the grow-out farming of mud crabs, and the potential solutions were discussed. The major constraints in the Scylla mud crabs' grow-out culture are (1) inadequate seed supply, (2) cannibalism, (3) disease outbreaks, and (4) no commercial formulated feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Crab carapace ulcers are mainly caused by fungal infections in crabs because mud crabs live on the bottom, so the spread of various fungal infections is common. Liew et al (2023) reported that disease outbreak of mud crab was one of the major constraints.…”
Section: Incidents Of Diseasesmentioning
confidence: 99%
“…Crab carapace ulcers are mainly caused by fungal infections in crabs because mud crabs live on the bottom, so the spread of various fungal infections is common. Liew et al (2023) reported that disease outbreak of mud crab was one of the major constraints.…”
Section: Incidents Of Diseasesmentioning
confidence: 99%